Penerapan Prinsip-Prinsip Etika Komunikasi Islam Dalam Manajemen Komunikasi Krisis Pada Lembaga Keagamaan - Najmuddin Azhar; Irfan Nur Hidayat; Ismail Mubarok (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
The purpose of this study is to identify the principles and ethics of Islamic communication used in interaction, as well as supporting and inhibiting factors that influence the application of Islamic communication principles by individuals and religious institutions. What principles of Islamic communication are used, and how do individuals and religious institutions apply them? Islamic communication and its elements for and against. This research was conducted through a qualitative approach that uses a descriptive approach. The results of this study show that the principles of Islamic communication are used by individuals and religious institutions in their communication, such as the principles of honesty, cleanliness, and positive speech. Religious institutions use these principles to establish good communication with each other. The ability to interact and communicate, mutual desire, desire, adaptability, and improved reading skills are components that help apply the principle. In addition, inhibiting factors that influence the application of Islamic communication principles include the environment. Communication has many explanations and receives special attention because Allah Almighty says: It means